Early evolution of sauropodomorphs: anatomy and phylogenetic relationships of a remarkably well-preserved dinosaur from the Upper Triassic of southern Brazil. Issue 4 (15th May 2018) - Müller, Rodrigo T; Langer, Max C; Bronzati, Mario; Pacheco, Cristian P; Cabreira, Sérgio F; Dias-Da-Silva, Sérgio
Abstract: An exceptional new specimen (CAPPA/UFSM 0035) of Buriolestes schultzi was discovered during recent fieldwork at the type locality of the taxon, which is Carnian in age (Late Triassic). This early sauropodomorph is peculiar owing to its faunivorous feeding habits, unusual amongst the members of this large omnivorous/herbivorous clade. The specimen incorporates new data on skeletal portions that have so far been unknown for B. schultzi, particularly regarding the skull and axial skeleton. As such, B. schultzi is now as complete as the best-known early dinosaurs, such as Eoraptor lunensis and Herrerasaurus ischigualastensis . A phylogenetic investigation fully supports B. schultzi as a sauropodomorph, corroborating the previous assignation. Despite the presence of traits found in Theropoda, distinct skeletal portions of B. schultzi do not share its morphospace in a morphological disparity analysis. We also propose an alternative evolutionary scenario for the first members of Sauropodomorpha: some Carnian taxa from South America form a monophyletic group instead of a series of low-diversity lineages paraphyletic with respect to Plateosauria.